Nanocomposite Starch Films: A New Approach for Biodegradable Packaging Materials. (20th March 2022) - Chavan, Prafull; Sinhmar, Archana; Sharma, Somesh; Dufresne, Alain; Thory, Rahul; Kaur, Maninder; Sandhu, Kawaljit Singh; Nehra, Manju; Nain, Vikash
Abstract: The growing interest in nano‐starch materials offers the opportunity to develop biomaterials for distinctive use in food, medicine, cosmetics, and other fields. The conceptual framework about the various changes in the properties of starch‐based films after incorporation of nano starch particles are reported. Starch‐based packaging films have not been widely used in the packaging industry, mainly because of their poor mechanical, barrier, and processing properties. To overcome such drawbacks, starch films are often made by integrating other filler materials such as nanoparticles into the starch matrix. The inclusion of starch nanoparticles in composite films leads to an overall change in the physicochemical, functional, and mechanical properties of the films. The nanocomposite films show novel features such as low solubility, reduced water vapor transmission rate, nontoxicity, and biodegradability thus making it a promising material for food and nonfood applications. Abstract : Edible films/coating can be used as an alternative for the plastic‐based packaging. Nanocomposite contains a material having one dimension in nano scale. The inclusion of starch nanoparticle improves the overall properties of starch film. Nanocomposite films have some novel features, i.e., low solubility, water vapor transmission rate, etc.